دور العقل في الفكر الإسلامي المعاصر: The Role of Aqal in Contemporary Islamic Thought - Shaikhah Binti Shikh Nasir; Rahmah Binti Ahmad H. Osman; Nurul Shafiqah Binti Muhamad Shatir; Min Hailong (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص یأتي هذا البحث بعد أن تفاقمت قضايا العصر الحديث التي نكاد نكون قد افتقرنا لوجود حل مناسب يعالج هذه القضايا من جذورها، بالإضافة إلى الركود الذي حدث للفكر الإسلامي، إذ أنَّ هذه الأزمة ستزول بإذنه تعالى وبجهود المسلمين الذين يستشعرون ميزة العقل التي وهبها الله لنا كي نتفكر ونتدبر ونتأمل، كما أنَّ العقل له دور كبير في إصلاح وتجديد الفكر الإسلامي المعاصر من خلال الاجتهاد الذي يأتي بعد مصادر التشريع الأساسية مكانةً، فالإسلام دين يحثنا على الاجتهاد في الأمور المعاصرة التي بزغت مع تطورات العصور على مر الأزمنة. Abstract This research derives after the aggravation of the issues of the modern era, which we almost lacked in the presence of an appropriate solution that treats these issues from their roots, in addition to the recession that occurred in Islamic thought, as this crisis will disappear by Allah’s permission and by the efforts of Muslims who believe the grace of Aqal that Allah grants us to think, and ponder, also Aqal has a major role in reforming and renewing contemporary Islamic thought through ijtihad, which comes after the basic sources of legislation position. Islam is a religion that motives us to search in contemporary matters that have emerged with the developments of the eras over the time.